DEVELOPING A BASIC UNDERSTANDING ABOUT SPOOF ATTACKS. - Ms. Harmandeep Kaur, Mr.Sukhwinder Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper provides an overview of spoofing and helps readers gain a better knowledge of the different types of assaults that are feasible, as well as how to protect themselves from such attacks. Spoofing attacks, in which an attacker replaces the original source address in the header with a new one in order to conceal their identity and location, continue to be one of the most devastating types of cyber-attacks. One of the most common spoofing attacks that users today are subjected to is the email spoofing attack, in which the spoofer obtains information about the email user before attacking through a fake email sender with fake messages and viruses to attack the user's system, mail list, and other resources, resulting in greater destruction to the email user who unknowingly opened and reacted to that mail.